FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN MENGKONSUMSIFAST FOODPADA REMAJA SMA KARTIKA V-1 BALIKPAPAN - Mahpolah, Mahpolah; Mahdalena, Mahdalena; Purnamasari, Vita (Lembaga Penelitian Universitas YARSI, 2008)
Current tendency shows that people in Indonesia prefer fast food for their meal which also influences the food consumption pattern in adolescent. It was estimated that every month, about 43.6% adolescent consume fast food, 6.1% among them had it a few times every week or almost everyday. The aim of this study was to find underlying factors related to the fast food consumption habit of adolescent at SMA Kartika V-1 Balikpapan year 2008. A cross sectional design was employed for observational study. The population study was all 640 students of SMA Kartika V-1 Balikpapan and number of subjects involved in the study were sampled proportionally from each class. Spearman correlation test was used to analyze the variables. The result showed that fast food consumption habit among adolescent in rare category was about 14.4%, sometimes was 8.3%, and often was 77.3%. Based on their age, there were about 25.7% was 15 years, 39.2% was 16 years and 35.1% was 17 years. About 62.9% and 37.1% of the students were good and average for their knowledge about nutrient respectively. Their pocket money were 67% and 33% above and below average respectively, whilst their parents? income were 1.0% under 853.000 rupiahs, 74.2% between 853.000?2.000.000 rupiahs, and 24.8% above 2.000.000 rupiahs. Their activity was 24.7 % less than 3 hours, 33.0% between 3?5 hours, and 24.7% more than 5 hours. In terms of food consumption pattern, about 41.2% was considered good, 41.2% average, and 17.6% was less or not good, whilst their body weight status about 76.3% was not obese and 23.7% was obese. Positive correlation was observed between age, total pocket money, parents? income, activity and body weight and fast food consumption habit, whereas no correlation was observed between nutrition knowledge, meal pattern and fast food consumption. It is suggested that the School should collaborate with health institution to provide better extra curricular training particularly on appropriate information related to fast food. In addition, it is also important for those adolescents toselect more healthy food rather than fast food.